Effect of hydrogen peroxide on color and whiteness of resin‐based composites. Issue 2 (29th November 2018) - Pecho, Oscar E.; Martos, Josué; Pinto, Karoline V. A.; Pinto, Karine V. A.; Baldissera, Rudimar A.
Abstract: Objective: To evaluate the influence of a 35% hydrogen peroxide gel on color and whiteness changes of resin‐based composites (RBC). Materials and Methods: Discs ( n = 10; shade A3.5 enamel; and 8 mm diameter and 2 mm thick) were fabricated from three RBC (DF‐ Durafill, Heraeus Kulzer; ED‐ IPS Empress Direct, Ivoclar Vivadent; and AP‐ Amelogen Plus, Ultradent Products). Three subgroups were obtained for each RBC: before bleaching ( T 0 ) and after first ( T 1 ) and second ( T 2 ) bleaching applications. A dental spectrophotometer (VITA Easyshade, Vita Zahnfabrik) was used to obtain CIELAB color coordinates and whiteness index for dentistry (WID ) in all periods. CIELAB ( Δ E ab * ) and CIEDE2000 ( ΔE 00 ) color differences were also obtained. Perceptibility (PT) and acceptability (AT) thresholds were used to analyze values of Δ E ab *, ΔE 00, and ΔWID . Two‐way analysis of variance (ANOVA; for L *, a *, b *, and WID ) and one‐wayANOVA and Tukey tests (for Δ E ab * and ΔE 00 ) were used to analyzed the results (α = 0.05). Results: L * and WID values from all RBC did not change after bleaching applications ( T 1 and T 2 ) ( P > .05). There were no significant differences in color differences ( Δ E ab * and ΔE 00 ) among all RBC evaluated after bleaching applications ( T 1 ‐ T 0 and T 2 ‐ T 0 ; P > .05). Regardless of the RBC, mean values of ΔE 00 between all different periods were always below 50%:50% PT value. Conclusions: The 35% hydrogen peroxide bleaching gel influences on color and whiteness of resin‐based composites. However, color changes were not clinically perceived and whiteness variations were clinically acceptable. Clinical Significance: Patients should be advised that existing composite restorations might not match the natural tooth color after bleaching, and their replacement may be required.